THE PRE-SERVICE TEACHERS' PERCEPTION ON INTEGRATING TECHNOLOGY IN TEACHING ENGLISH FOR YOUNG LEARNERS - Kharisma Naidi Warnanda Sabgini; Triastama Wiraatmaja (PROJECT (Professional Journal of English Education), 2022)
Amidst the growing usage of technology in the classroom, there is little knowledge about the study of pre-service teachers' perception on using ICT in young learners' classrooms. During the teaching practice of English for Young Learners, the researchers notices that the pre-service teachers practice technology in their classroom. This study focuses on the perception of the pre-service teachers on using technology in the English for Young Learner classroom. The study is a mixed quantitative-qualitative study. The quantitative study data is obtained using a questionnaire to gather numerical data. Meanwhile, the qualitative data is obtained from in-depth interviews to discover more and deeper discoveries about the study. The study finds out that the pre-service teachers have a positive perception about the usage of technology. Furthermore, based on the in-depth interview, the researchers discover that the technology integration makes the pre-service teachers more confident.